2010
DOI: 10.1007/s11558-010-9091-4
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming international governance: The environment, gender, and IO performance in the European Union

Abstract: International organizations (IOs) have moved increasingly in recent years to adopt cross-cutting mandates that require the "mainstreaming" of particular issues, such as gender equality or environmental protection, across all IO policies. Successful IO performance with respect to such mandates, we hypothesize, is determined in large part by the use of hard or soft institutional measures to shape the incentives of sectoral officials whose cooperation is required for successful implementation. We test this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 26 publications
(23 reference statements)
0
46
0
Order By: Relevance
“…Regarding the first, a common gap identified is that the implementation of integrated strategies is highly sectorized at best, and limited to only one or a few government sectors out of a whole range of targeted sectors at worst (Drimie and Ruysenaar 2010;Vince 2015;Casado-Asensio and Steurer 2016). For example, studies of EPI strategies found that it is often only the environmental ministries or directorate-generals that engage in genuine implementation, whereas implementation beyond the environmental sector is generally weak (Jordan and Lenschow 2000;Hertin and Berkhout 2003;Pollack and Hafner-Burton 2010;Russel and Jordan 2010).…”
Section: Intermediate Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the first, a common gap identified is that the implementation of integrated strategies is highly sectorized at best, and limited to only one or a few government sectors out of a whole range of targeted sectors at worst (Drimie and Ruysenaar 2010;Vince 2015;Casado-Asensio and Steurer 2016). For example, studies of EPI strategies found that it is often only the environmental ministries or directorate-generals that engage in genuine implementation, whereas implementation beyond the environmental sector is generally weak (Jordan and Lenschow 2000;Hertin and Berkhout 2003;Pollack and Hafner-Burton 2010;Russel and Jordan 2010).…”
Section: Intermediate Outcomesmentioning
confidence: 99%
“…Hereby, it should be noted that not all integrated strategies aim at having a societal impact. For example, EU Environmental Policy Integration (EPI) commitments, as laid down in the Commission EPI program, the 1997 Amsterdam Treaty, and the Cardiff Process, are primarily targeted at changing policy-making efforts (Schout and Jordan 2005;Pollack and Hafner-Burton 2010). Studies that do reflect on eventual outcomes provide diffuse but largely negative insights, whereby most researchers make the side-note that their analyses do not well-isolate the effects of integrated strategies from other factors (Section 4.4).…”
Section: Eventual Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the primary attraction of IAs, which obviously have a strong rationalistic appeal, would be that of making governments and regulatory agencies rely more on evidence-based analysis and of making them more accountable (Radaelli and Meuwese, 2010). However, the execution of IAs has not met initial expectations: numerous concerns have been raised on their overall quality, particularly the quantification of costs and benefits of alternative proposals and the effective involvement of stakeholders (Kirkpatrick and Franz, 2007;Pollack and Hafner-Burton, 2010;Torriti, 2010). The IA procedure was originally seen by the European Commission as a 'a powerful mechanism' to further advance the promotion of PCD -and was further stressed by the 2009 revised guidelines, stating explicitly that more attention would have to be paid to assessing the impact of all EU policies on developing countries (European Commission, 2009a) -and corresponds to the political commitment expressed by the EU's Foreign Affairs Council, which called for an 'evidence-based and result-oriented approach to promoting PCD' (Council, 2012).…”
Section: Pcd In Practise: Reforming Agricultural and Fisheries Policiesmentioning
confidence: 99%